Evaluation of biventricular longitudinal myocardial function in normal fetuses at different gestational ages using ultrasonic velocity vector imaging - Hou, Min; Liu, Liu; Xie, Jun-Min; Duan, Xiao-Jing; Lv, Xiao-Lan; Li, Xiao-Qing; Zhang, Qin (Frontiers in Pediatrics, 2022)
Objective: This study aimed to evaluate biventricular myocardial function and biventricular longitudinal global myocardial function of fetuses at different gestational weeks using ultrasonic velocity vector imaging. Methods: A total of 127 pregnant women were enrolled and divided into five groups according to the gestational age of their fetuses. The velocity, strain, and strain rate of the left and right ventricles were measured, and these biventricular parameters were compared between the groups. The global parameters of the biventricular myocardium were also compared. Results: A pairwise comparison revealed that the differences in biventricular velocity and strain rate between groups in adjacent gestational weeks were not statistically significant (P > 0.05), but velocity increased with gestational age. A comparison of fetal longitudinal global myocardial parameters revealed that the global velocity, strain, and strain rate of the right ventricle were higher than those of the left ventricle, and the differences were statistically significant (P < 0.05) in all groups. Conclusion: The peak velocities of the fetal left and right ventricles increased with gestational age, but the global strain and strain rate did not, suggesting that fetal myocardial function is mature and constant in the middle and late stages of pregnancy and can more reliably reflect myocardial deformation. The peak systolic velocity, global strain, and peak strain rate of the right ventricle were higher than those of the left ventricle, suggesting that the right ventricle dominates longitudinal systolic movement from the second trimester of pregnancy.